International Collaboration for Capacity Development in Higher Education Leadership and Management: the Uganda-Finland Initiative - Bisaso, Ronald; Hölttä, Seppo (International Journal of African Higher Education, 2017)
Changes in higher education leadership and management in sub-Saharan Africa have been epitomised by public sector reforms sanctioned by the World Bank since the beginning of the 1990s. Recently, emerging forces redefning higher education have entailed country-specifc development cooperation instruments in countries such as Finland, Norway, Austria and The Netherlands. The overriding emphasis is on the role of higher education institutions in the socio–economic transformation of developing countries, partly realisable through robust higher education leadership. However, sustainable academic and professional knowledge bases in the form of non-degree, masters and doctoral programmes to build such leadership and management capacity are elusive. Drawing on the Uganda-Finland capacity development initiative, a stakeholder analysis was conducted through document reviews. The fndings and conclusions illuminate the complementary roles of stakeholders and the necessity of integrating professional career pathways into masters and doctoral higher education leadership and management programmes implemented through international collaboration. Les changements dans la direction et la gestion de l’enseignement supérieur en Afrique sub-saharienne ont été illustrés par des réformes du secteur public sanctionnées par la Banque Mondiale depuis le début des années 1990. Récemment, l’émergence de forces redéfnissant l’enseignement supérieur a engendré le développement par des pays comme la Finlande, la Norvège, l’Autriche et les Pays Bas d’instruments de coopération pour le développement spécifques à chaque pays. L’accent a été mis sur le rôle joué par les institutions d’enseignement supérieur dans la transformation socio-économique des pays en voie de développement, rôle qui ne peut être réalisé sans une direction robuste. Cependant, il manque des bases de savoir académique et professionnel durables sous forme de cursus non diplômants, de masters et de doctorats, pour former de telles capacités de direction et de gestion. Une analyse des parties prenantes a été réalisée grâce à une revue de textes portant sur l’exemple de l’initiative Ouganda – Finlande pour le développement des capacités. Les résultats et conclusions soulignent le rôle complémentaire des parties prenantes et la nécessité de professionnaliser les carrières de direction et de gestion de l’enseignement supérieur au moyen de masters et de doctorats établis à travers des coopérations internationales.